Epigenetics of Modified DNA Bases: 5-Methylcytosine and Beyond - Kumar, Suresh; Chinnusamy, Viswanathan; Mohapatra, Trilochan (Frontiers in Genetics, 2018)
Modification of DNA bases plays vital roles in the epigenetic control of gene expression in both animals and plants. Though much attention is given to the conventional epigenetic signature 5-methylcytosine (5-mC), the field of epigenetics is attracting increased scientific interest through the discovery of additional modifications of DNA bases and their roles in controlling gene expression. Theoretically, each of the DNA bases can be modified; however, modifications of cytosine and adenine only are known so far. This review focuses on the recent findings of the well-studied cytosine modifications and yet poorly characterized adenine modification which serve as an additional layer of epigenetic regulation in animals and discuss their potential roles in plants. Cytosine modification at symmetric (CG, CHG) and asymmetric (CHH) contexts is a key epigenetic feature. In addition to the ROS1 family mediated demethylation, Ten-Eleven Translocation family proteins-mediated hydroxylation of 5-mC to 5-hydroxymethylcytosine as additional active demethylation pathway are also discussed. The epigenetic marks are known to be associated with the regulation of several cellular and developmental processes, pluripotency of stem cells, neuron cell development, and tumor development in animals. Therefore, the most recently discovered N6-methyladenine, an additional epigenetic mark with regulatory potential, is also described. Interestingly, these newly discovered modifications are also found in the genomes which lack canonical 5-mC, signifying their independent epigenetic functions. These modified DNA bases are considered to be important players in epigenomics. The potential for combinatorial interaction among the known modified DNA bases suggests that epigenetic codon is likely to be substantially more complicated than it is thought today.